Concomitant Expression of Inhibitory Molecules for T cell Activation Predicts Poor Survival in Patients with Esophageal Squamous Cell Carcinoma - Chen, Zhijun; Cao, Kexin; Zhang, Jinghang; Liu, Zhuangzhuang; Lu, Liaoxun; Qi, Bo; Shi, Lijin; Huang, Rong; Zhao, Song (Current Cancer Drug Targets, 2021)
Background: Esophageal squamous cell carcinoma (ESCC) is a major subtype of esophageal cancers. The five-year survival rate of ESCC is low, and molecular targets for ESCC treatment and prognosis assessment are very limited. T cells are critical for the clearance of cancer cells, and blockade of co-inhibitory molecules for T cell activation has emerged as a promising therapy to treat cancer patients. However, in ESCC patients, co-inhibitory molecules regulating T cell activation are poorly documented. Objective: We aim to evaluate how the presence of inhibitory check-point molecules in T cells could impact the survival of patients. Methods: We performed a follow-up study of 161 patients undergoing resection of esophageal carcinoma from February 2014 to December 2015, by immunohistochemical staining of six co-inhibitory molecules for T cell activation, namely PD-1, CTLA-4, TIM-3, LAG-3, BTLA and A2AR. Expression of each of the six co-inhibitory molecules was analyzed for its correlation with patient survival by Kaplan-Meier survival analysis. We also applied Kaplan-Meier analyses to evaluate the concomitant expression of co-inhibitory molecules and their correlation with patient survival. Results: We found that levels of PD-1, TIM-3 and BTLA can be used as independent prognostic factors for the overall survival of patients with ESCC. More importantly, our study found that the co-expression of PD-1 and TIM-3, PD-1 and BTLA, TIM-3 and BTLA significantly reduced the survival of patients with ESCC (P<0.05). Conclusion: Therefore, our results suggest the necessity of evaluating the tumor tissue expression of co-inhibitory molecules and targeting co-expressed molecules in immunotherapies for ESCC patients.
Keywords: ESCC